Tiny House, Big Learning (pp. 18--30) - Driskell, Shannon O. S.; Gold, Lindsay A.; Herick, Dave (Ohio Journal of School Mathematics, 2020)
The authors introduce the Tiny House Project—an interdisciplinary, problem-based Science,Technology, Engineering, Arts, and Mathematics (STEAM) activity. The project was designed to promotethe implementation of the Standards of Mathematical Practice (SMP). As 5th graders engaged in theproject, they explored the concepts of floor plans, 2-D shapes, parallel and perpendicular line segments,angles, scale drawings, measurement, perimeter, area, 3-D models (using Planner 5D), and spatial reason-ing. Moreover, they strengthened their problem solving, planning, and designing skills as they connectedmeasurement and geometry to the real-world context of constructing a house.